2006
DOI: 10.1073/pnas.0507261103
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPβ is a critical mediator of steroid hormone-regulated cell proliferation and differentiation in the uterine epithelium and stroma

Abstract: During early pregnancy, steroid hormones estrogen (E) and progesterone (P) regulate a complex series of interactions between the implanting embryo and the uterus by controlling the proliferation and differentiation of uterine epithelium and stroma in a timely manner. To identify the steroid-regulated genes that control these functions, we performed messenger RNA profiling of mouse uterine tissues at the time of implantation. Our analysis revealed that the expression of the transcription factor CCAAT͞enhancer-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
138
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(144 citation statements)
references
References 35 publications
5
138
0
1
Order By: Relevance
“…Further analysis revealed that the effect of cAMP on Hmgn1 expression was mediated by C/EBPb which was essential for decidualization and controlled the differentiation of stromal cells during decidualization. 14,15 In the uterine stromal cells undergoing decidualization, C/EBPb might induce the expression of Hmgn1. Moreover, overexpression of Hmgn1 could improve the expression of Prl8a2 and Prl3c1 in the C/EBPb siRNA-transfected stromal cells, whereas knockdown of Hmgn1 prevented the C/EBPbinduced up-regulation of Prl8a2 and Prl3c1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further analysis revealed that the effect of cAMP on Hmgn1 expression was mediated by C/EBPb which was essential for decidualization and controlled the differentiation of stromal cells during decidualization. 14,15 In the uterine stromal cells undergoing decidualization, C/EBPb might induce the expression of Hmgn1. Moreover, overexpression of Hmgn1 could improve the expression of Prl8a2 and Prl3c1 in the C/EBPb siRNA-transfected stromal cells, whereas knockdown of Hmgn1 prevented the C/EBPbinduced up-regulation of Prl8a2 and Prl3c1.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Because C/EBPb was also expressed in the decidualized cells and overlapped with Hmgn1, we assumed that there was a relationship between C/EBPb and Hmgn1 during decidualization. To elucidate the relationship, we first studied the regulation of Hmgn1 on C/EBPb.…”
Section: Effects Of Hmgn1 On Decidualizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the years, the decidualization process has been studied extensively and the use of transgenic mice has not only demonstrated its necessity for pregnancy but has made it possible to identify critical genes involved in this process. The genes important for decidualization identified thus far include progesterone receptor A (Lydon et al, 1995), homeobox (HOX) A10 (Satokata et al, 1995), cyclooxygenase 2 (Lim et al, 1997), leukemia inhibitory factor (Stewart et al, 1992;Stewart and Cullinan 1997), interleukin 11 receptor (Robb et al, 1998), Hoxa11 (Gendron et al, 1997), FK506 binding protein 4 (Tranguch et al, 2007), CCAAT/enhancer binding protein beta (Mantena et al, 2006), Indian Hedgehog (Lee et al, 2006), steroid receptor coactivator-1 and steroid receptor coactivator-2 and -1 (Mukherjee et al, 2006).…”
Section: Introductionmentioning
confidence: 99%